Transcriptome analysis of Ruditapes philippinarum hepatopancreas provides insights into immune signaling pathways under Vibrio anguillarum infection. Issue 64 (May 2017) - Ren, Yipeng; Xue, Junli; Yang, Huanhuan; Pan, Baoping; Bu, Wenjun
Abstract: The Manila clam, Ruditapes philippinarum, is one of the most economically important aquatic clams that are harvested on a large scale by the mariculture industry in China. However, increasing reports of bacterial pathogenic diseases have had a negative effect on the aquaculture industry of R. philippinarum . In the present study, the two transcriptome libraries of untreated (termed H) and challenged Vibrio anguillarum (termed HV) hepatopancreas were constructed and sequenced from Manila clam using an Illumina-based paired-end sequencing platform. In total, 75, 302, 886 and 66, 578, 976 high-quality clean reads were assembled from 101, 080, 746 and 99, 673, 538 raw data points from the two transcriptome libraries described above, respectively. Furthermore, 156, 116 unigenes were generated from 210, 685 transcripts, with an N50 length of 1125 bp, and from the annotated SwissProt, NR, NT, KO, GO, KOG and KEGG databases. Moreover, a total of 4071 differentially expressed unigenes (HV vs H) were detected, including 903 up-regulated and 3168 down-regulated genes. Among these differentially expressed unigenes, 226 unigenes were annotated using KEGG annotation in 16 immune-related signaling pathways, including Toll-like receptor, NF-kappa B, MAPK, NOD-like receptor, RIG-I-like receptor, and the TNF and chemokine signaling pathways. Finally, 20, 341 simple sequence repeats (SSRs) and 214, 430 potential single nucleotide polymorphisms (SNPs) were detected from the H and HV transcriptome libraries. In conclusion, these studies identified many candidate immune-related genes and signaling pathways and conducted a comparative analysis of the differentially expressed unigenes from Manila clam hepatopancreas in response to V. anguillarum stimulation. These data laid the foundation for studying the innate immune systems and defense mechanisms in R. philippinarum. Highlights: First hepatopancreas transcriptome of R. philippinarum aimed to comparative analyse the unigenes injected Vibrio anguillarum . We obtained 101, 080, 746 and 99, 673, 538 raw reads from two transcriptome groups and assembled into 156, 116 unigenes. A number of 4071 DEGs were identified and 226 DEGs were annotated in 16 immune-related signal pathways. We obtained 20, 341 SSRs and 214, 430 potential SNPs in this study.